PELATIHAN ECO FRIENDLY PACKAGING DI BANK SAMPAH GULON ASRI SURAKARTA - Endri Sintiana Murni; Nurhayatu Nufut Alimin; Endang Sri Handayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Gulon Asri Waste Bank is a place used to collect waste that has been sorted first. The selected waste is then collected and made crafts. Garbage Bank with good potential to be able to increase people's income. Making packaging at the Gulon Asri Waste Bank is a form of support for the creativity of the community that makes interesting works from waste. This program aims to help the Gulon Asri Waste Bank by utilizing leftover fabrics to be developed as packaging so as to increase the commercial value of the product. The public can create economical value packaging with attractive packaging. Then, the waste bank community can also increase environmental and community awareness by empowering existing resources, increasing motivation, and community creativity. The community can also develop creativity in making sustainable and environmentally friendly packaging so that the products created by the waste bank have attractive packaging by utilizing cloth waste as well and have high selling power.